Respuesta :
6 x 1/6 + 11 x 2
Since multiplication comes before addition in PEMDAS, you’ll need to do multiplication first. The first multiplication in this expression is 6 x 1/6 which can also be written as 6/1 x 1/6
6/1 x 1/6 = 1
The second multiplication in this equation is 11 x 2
11 x 2 = 22
Now you can add both of the numbers and you’d get 23 :)
1 + 22 = 23
Since multiplication comes before addition in PEMDAS, you’ll need to do multiplication first. The first multiplication in this expression is 6 x 1/6 which can also be written as 6/1 x 1/6
6/1 x 1/6 = 1
The second multiplication in this equation is 11 x 2
11 x 2 = 22
Now you can add both of the numbers and you’d get 23 :)
1 + 22 = 23